A short course in grammar : a course in the grammar of standard written English - Hopper, Paul J. (W. W. Norton, 1999)
The English language. Words. Phrases. Sentences and their parts. Objects and adjuncts. The verb phrase. Prepositional phrases and adverbials. The noun phrase I, II, Negation. The passive. Coordination...